Antonio Gómez-Moriana, Discourse analysis as sociocriticism. The Spanish Golden Age. University of Minnesota Press, Minneapolis, 1993; 179 pp. - Barreras, Isabel (El Colegio de México, 1994)
Se reseñó el libro: Discourse analysis as sociocriticism. The Spanish Golden Age.